Histoire de la Justice au Luxembourg (1795 à nos jours) Institutions - Organisation - Acteurs - Fritz, Vera / Scuto (Studien zur transnationalen Zeitgeschichte Luxemburgs, 2022)
This book dives into the origins of the judicial organization of Luxembourg by tracing its evolution from the establishment of contemporary jurisdictions under the "Directoire", the "Consulate" and the "Empire", to the constitutional reform of the 2000s. Illustrated with photographs and archival documents, it is intended for both specialist and non-specialist readers.